Mitigating Budget Slack in Remote Work Environments: Evidence from Indonesian Shared Service Centers - Setyorini, Noni; Lestari, Dwirani Fauzi (Indonesian Scientific Publication, 2024)
Remote work, accelerated by the COVID-19 pandemic, has transformed operational models across Indonesian Shared Service Centers (SSCs), offering flexibility but also creating challenges in maintaining budgetary discipline. This study examines how remote work and incentive structures shape the formation of budget slack, with particular attention to the moderating role of trust and organizational integration. Employing a quasi-experimental Difference-in-Differences (DiD) design, data were drawn from surveys, operational logs, and HR records across SSC units in Indonesia, with budget slack measured using validated Likert-scale instruments. The DiD estimations also included interaction terms for trust and incentives to test moderating effects. The findings indicate that remote work tends to increase budget slack due to reduced managerial oversight, yet performance-based incentives such as KPI-linked bonuses and ESOPs significantly mitigate this effect, especially in environments characterized by high managerial trust. The study underscores the need for holistic control frameworks combining digital tools, human centered leadership, and policy coordination. Effective SSC governance in hybrid environments requires incentive alignment, trust building, and cross functional collaboration.